Exchange policy credibility through the lens of the carry trade: The Mexican peso and the Brazilian real - Carlos Fernańdez-Herraiz; Antonio Javier Prado Domińguez; Carlos Pateiro-Rodriguez; Jesus M. Garcia-Iglesias (European Journal of Government and Economics (EJGE), 2018)
Exchange credibility is a valuable asset for currency policymakers. In this article we intend to analyse exchange credibility from the perspective of carry trade speculators. Global speculators' access to shadow banking financing allows them to build dynamic carry trade strategies that are a source of potential financial instability. Our view is that the existence of dynamic carry trade opportunities offers a tool for monitoring how market participants asses the credibility of exchange policies. We use the long term performance of different carry trade dynamic specifications to understand how different is the market view of exchange policy credibility in the case of two leading Latin America countries, Mexico and Brazil. Our empirical research covers data from May of 2000 to May 2018. In light of the evidence presented, we recognize that Mexican peso exchange policy is considered credible but Brazilian real exchange policy is not considered credible during the sample period.
Keywords: 330; Currency carry trade; Sharpe ratio; exchange policy credibility; shadow banking